Rammed earth construction cutting-edge research on traditional and modern rammed earth - Ciancio, Daniela; Beckett, Christopher (CRC Press/Balkema, 2015)
Rammed Earth Construction: Cutting-Edge Research on Traditional and Modern Rammed Earth is a collection of peer-reviewed papers presented at the First International Conference on Rammed Earth Construction (ICREC2015, University of Western Australia, Perth, Western Australia, 10-13 February 2015) by academics, engineers and rammed earth practitioners from around the world